2022
DOI: 10.11591/ijeecs.v25.i2.pp1103-1114
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic elliptic map for speech encryption

Abstract: Using a new key management system and Jacobian elliptic map, a new speech encryption scheme has been developed for secure speech communication data. Jacobian elliptic map-based speech encryption has been developed as a novel method to improve the existing speech encryption methods' drawbacks, such as poor quality in decrypted signals, residual intelligibility, high computational complexity, and low-key space. Using the Jacobian elliptic map as a key management solution, a new cryptosystem was created. The prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Nasreen and Muthukumar [15] proposed an audio encryption technique that relies on a dynamical system incorporating fractional derivatives, demonstrating chaotic behavior across a spectrum of fractional orders and parameter values. Hazaimeh et al [16] proposed a block cipher technique to encrypt speech based on a Jacobian elliptic map. By merging an infinite collapse map (1D-ICM) with a logistic map, Wu et al [17] suggested an audio encryption technique based on a 2Dlogistic-nested-infinite-collapse (2D-LNIC).…”
Section: Related Workmentioning
confidence: 99%
“…Nasreen and Muthukumar [15] proposed an audio encryption technique that relies on a dynamical system incorporating fractional derivatives, demonstrating chaotic behavior across a spectrum of fractional orders and parameter values. Hazaimeh et al [16] proposed a block cipher technique to encrypt speech based on a Jacobian elliptic map. By merging an infinite collapse map (1D-ICM) with a logistic map, Wu et al [17] suggested an audio encryption technique based on a 2Dlogistic-nested-infinite-collapse (2D-LNIC).…”
Section: Related Workmentioning
confidence: 99%
“…The burgeoning exchange of multimedia data via open networks and the internet necessitates robust and reliable security measures to ensure confidentiality and prevent unauthorized access. Among various solutions, data encryption [1] has emerged as a key approach, where data is manipulated to render it unreadable, invisible, or impenetrable during transmission via encryption algorithms. As such, the importance of data encryption has been underscored in numerous applications, and several schemes have been developed to enhance the security and confidentiality of sensitive data [2].…”
Section: Introductionmentioning
confidence: 99%
“…Waveform analysis: proved that the waveforms are aperiodic, and waveform's time domain has noncyclical properties [11], [12]. Figure 3…”
mentioning
confidence: 99%